Substantiation of the Parameters of Regenerative Devices for Mining Dump Trucks - Umrzakov Javahir Abdurazzak oglu (Research Parks Publishing LLC, 2022)
At mining enterprises with an open pit, a special role belongs to quarry transport. It is not only the most complex and laborious link in the technological process of developing mineral deposits, but to a large extent determines the conditions and performance of other links and the enterprise as a whole. In the cost of mining, the share of transport costs reaches 50-70%.